ANALYSIS OF AREA CHANGES IN LAND VEGETATION MANGROVE COASTAL REGENCY OF CENTRAL TAPANULI REGENCY NORTH SUMATERA PROVINCE USING LANDSAT IMAGE DATA ANALYSIS - Fuady, Muhammad Ikhram Fuady Ikhram; Mubarak, Mubarak; Samiaji, Joko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTGeographical Information System (GIS) method is one of the methods that began to be used and developed in Indonesia in observing and analyzing spatial changes in an area. The study was conducted in March - April 2019 in Central Tapanuli Regency, North Sumatra Province. The purpose of the study was to analyze changes in land cover of mangrove vegetation and mangrove vegetation index based on images taken from different times at intervals of 5 years, namely from 1998 to 2018, the category of density obtained in the field was analyzed based on Minister of Environment Decree No. 201 of 2004 concerning Standard Criteria and Guidelines for Mangrove Damage Determination. The results showed that environmental ecological conditions support the existence of mangroves. Morphological identification was obtained by 11 species from 8 families of mangrove vegetation. The area of mangrove vegetation in 1998 was 9510 ha and the area of mangrove in 2018 was 1,779 ha. Over a period of 20 years (1998 - 2018) there was a change in the reduction in the area of mangroves covering an area of 7,731 ha, with a total of 81% of mangroves lost during the last 20 years. Tree density calculation data at 3 stations are 1622 ind / ha, 1,444 ind / ha and 2,133 ind / ha in the meeting category at station I and III and medium at station II. Puppies density at 3 stations namely 4,355 ind / ha, 6,444 ind / ha and 4,400 ind / haKeywords: Central Tapanuli Regency, Mangrove, Changes in Area, NDVI,Density.